Pengaruh Jumlah Taksiran dan Uang Pinjaman terhadap Laba Bersih pada Perum Pegadaian Syari'ah Kota Lhokseumawe - Damanhur; Darwina, Leni (Jurnal Aplikasi Manajemen, 2011)
This study aims to determine the influence of the number of estimates and borrowing money against the net profit on Shariah Pawnshop Lhokseumawe. The data used are secondary data were processed using multiple linear regression analysis through SPSS (Statistical Package for Social Science) version 12.0.The results obtained correlation value (R) of 0.953, a very strong relationship between the estimated and borrowed money in affecting net income. Adjusted R square value of 0.895 means that 89.5% of the changes in the dependent variable is influenced by the independent variable and the remaining 10.5% is influenced by other variables that are not observed in this study (error term). The results obtained by testing hypotheses simultaneously calculated F value> Ftable (64.661> 3.81), means the total estimated number of simultaneous variables (X1) and borrowing money (X2) are jointly significant effect on net income at the Pawnshop syari'ah Lhokseumawe. The test results obtained by partial hypothesis tcount variable amount estimated (X1) of 0.601 while ttable of 2.1604, which means that the value of the estimated partial effect on net income. Variable loan money (X2) equal to 10.437, while ttable of 2.1604, which means that borrowing money is partially an effect on net income. Suggested to Shariah Pawnshop Lhokseumawe in order to be a motivator for other financial institutions in helping people who need them.